2020
DOI: 10.2174/1570193x15666181031111117
|View full text |Cite
|
Sign up to set email alerts
|

Aryl-Aryl Bond Formation by Ullmann Reaction: From Mechanistic Aspects to Catalyst

Abstract: Aryl-aryl bond formation is one of the most important tools in modern organic synthesis. Therefore, there is a high level of interest to develop green, effective reaction system to obtain biaryls. This review summarized the recent advances in the metal-catalyzed Ullmann reaction in which the aryl-aryl bond was formed directly. Furthermore, different types of catalytic mechanisms, especially the surface reaction, have been summarized to help the design of the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 104 publications
0
21
0
Order By: Relevance
“…Gold catalysis is one of the most captivating topics in Organic Chemistry [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In recent years, particular attention has been devoted to gold catalyzed CAH bond activations as a strategic tool for the formation of new CAC bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Gold catalysis is one of the most captivating topics in Organic Chemistry [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In recent years, particular attention has been devoted to gold catalyzed CAH bond activations as a strategic tool for the formation of new CAC bonds.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction can be catalyzed at much lower temperatures by some Au and Pd NPs and NCs. [145][146][147][148][149][150][151][152][153][154][155] Obviously the NPs or NCs not only serve as catalysts for activation of the aryl-halogen bonds and aryl-aryl reductive elimination, but along the catalytic cycle they also behave as electron reservoirs trapping the required electrons provided by the DMF solvents. [155] It is most probably the electron-reservoir nature of the NPs and NCs that allows conducting these reactions of the order of 50 to 100 °C lower than using the traditional Cu catalysts (Scheme 6).…”
Section: Ncs and Nps As Electron Reservoir Catalysts In The Ullmann Coupling Reactionmentioning
confidence: 99%
“…Rodionov's group demonstrated that a combination of thiolate groups and linear semi-fluorinated chains effectively stabilized the NPs against aggregation, while preserving the catalytic activity of AuNPs. 19 Various other reports using AuNP catalysts [20][21][22][23][24] have been recently and comprehensively reviewed by Ding's group, 25 and particular attention to carboncarbon bond formation catalysts has been drawn by Garcia's group to the use of MOF-based catalysts. 26,27 NP catalysts are indeed particularly efficient for a large variety of reactions and withstand homogeneous as well as heterogeneous reaction conditions.…”
Section: -18mentioning
confidence: 99%